Pengawasan Dinas Lingkungan Hidup Kabupaten Toba - Daniel Adiasto Pangaribuan; Harapan Tua Ricky Freddy S (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2021)
Development in the industrial sector also causes negative impacts that can threaten the preservation of the surrounding environment, the importance of monitoring companies that may have negative impacts. Environmental pollution carried out by PT Toba Pulp Lestari which occurs in the Toba Regency area shows that the supervision carried out by the Toba Regency Environmental Service has not been optimal. The purpose of this research is to see how the supervision carried out by the Environmental Office of Toba Regency in supervising environmental pollution by PT Toba Pulp Lestari and what factors are hindering the supervision carried out by the Environmental Office of Toba Regency in overcoming environmental pollution by PT Toba Pulp Lestari.